Kewenangan Rumah Tahanan di Indonesia dalam Kebijakan Penanganan Kelebihan Kapasitas (Overcrowded) - Jalaluddin; Hamdi, Syaibatul; Dasmiyana (Prodi Hukum Tata Negara Islam (Siyasah Syar'iyyah) STAIN Teungku Dirundeng Meulaboh, 2024)
A prison or detention center (RUTAN) is a correctional institution that has an important role in developing prisoners so that they can re-adapt to society. However, a significant problem arises from the excess capacity or overcrowding that occurs in many prisons in Indonesia. This situation causes the available facilities, such as beds, sanitation and health services, to become inadequate. As a result, this affects the physical and mental condition of the prisoners, as well as hampering the success of the development program being implemented. Efforts to overcome existing problems, referring to the authority of detention centers, are important to be studied in order to understand the capacity of detention centers in carrying out their authority regarding excess capacity in correctional institutions. The research method used is a socio-legal approach, which is designed to address problems of social inequality, including due to the ineffectiveness of authority. As a conclusion, detention centers have dynamic authority in dealing with the problem of excess capacity of existing prisoners, this is outlined in the Minister of Law and Human Rights Regulation Number 11 of 2017 concerning the grand design for handling overcrowding in state detention centers and correctional institutions, explaining the solution. and stages and steps in dealing with Overcrowded itself.